Addressing New Problems in Primary Care Outpatient Consultations Using the TOPIC Model - Cuba-Fuentes, María sofía (2025)
In outpatient consultations, physicians utilize tools to optimize time and enhance their clinical interviewing skills, as these interactions can be complex (e.g., new problems, chronic conditions, mental health issues). New problems can be addressed using the TOPIC model (Tasks Oriented to Outpatient Care Processes), which sets standardized tasks and processes to identify needs in this type of visit. This article describes this tool.